2005
DOI: 10.1111/j.1365-2958.2005.04942.x
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis‐induced platelet aggregation in plasma depends on Hgp44 adhesin but not Rgp proteinase

Abstract: SummaryEvidence from recent epidemiological studies suggests a link between periodontal infections and increased risk of atherosclerosis and related cardiovascular and cerebrovascular events in human subjects. One of the major pathogens of periodontitis, Porphyromonas gingivalis, has the ability to aggregate human platelets in platelet-rich plasma (PRP). Mechanism of P. gingivalis -induced platelet aggregation in PRP was investigated. Proteinase inhibitors toward Arg-gingipain (Rgp) and Lys-gingipain (Kgp) did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 57 publications
(63 reference statements)
3
74
0
Order By: Relevance
“…Oral bacteria, Porphomonas gingivalis expresses a surface protein called hgp44 which induces platelet aggregation in an FcγRIIA dependent manner [73]. The authors demonstrated that IgG was critical for the interaction.…”
Section: Indirect Interaction With Fcγriiamentioning
confidence: 86%
“…Oral bacteria, Porphomonas gingivalis expresses a surface protein called hgp44 which induces platelet aggregation in an FcγRIIA dependent manner [73]. The authors demonstrated that IgG was critical for the interaction.…”
Section: Indirect Interaction With Fcγriiamentioning
confidence: 86%
“…Proteinase inhibitors of Arg-gingipain (Rgp) and Lys-gingipain (Kgp) did not suppress P. gingivalis-induced platelet aggregation in PRP, whereas the Rgp inhibitor markedly inhibited P. gingivalis-induced platelet aggregation when washed platelets were used. Mutant analysis revealed that P. gingivalis-induced platelet aggregation in PRP depended on Rgp-, Kgp-and hemagglutinin A (HagA)-encoding genes that intragenically coded for adhesins such as Hgp44 [25]. Future studies in our laboratory will focus on the molecular mechanisms of the signal pathway in P. gingivalis-induced platelet aggregation, since they are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…5 Evidence from recent epidemiological studies suggests a link between periodontal infections and risk of vascular events. 6 DNA of typical periodontal pathogens was demonstrated in atheromatous plaques, and a low or moderate association between existing periodontitis and the development of vascular events had been observed. [5][6][7] Another crucial point deals with the socioeconomic status of the enrolled population being known that there is a relation between adverse socioeconomic conditions and both dental diseases and atherosclerosis.…”
Section: Predisposition To Carotid Atherosclerosis In Icaras Dental Smentioning
confidence: 98%